2016
DOI: 10.1177/0300060516645004
|View full text |Cite
|
Sign up to set email alerts
|

Ramipril + amlodipine and ramipril + hydrochlorothiazide fixed-dose combinations in relation to patient adherence

Abstract: ObjectiveTo compare 1-year treatment adherence of ramipril + amlodipine and ramipril +hydroclorothiazide fixed-dose combination therapies in patients with hypertension.MethodsData were extracted from the database of the National Health Insurance Fund of Hungary. Treatment adherence was modelled using survival analysis.ResultsAt 2 months after initiation of treatment, 42% of patients using ramipril +hydrochlorothiazide (n = 28,800) had discontinued treatment, compared with 0% of patients using ramipril + amlodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
2
0
3
Order By: Relevance
“…All 29 studies reported on adherence and/or persistence in patients taking SPC therapy for hypertension. Four studies were RCTs (14%) [35,37,38,46]; the remainder (n ¼ 25; 86%) were observational studies [14,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]36,[39][40][41][42][43][44][45]47] (Table S3, http://links.lww.com/HJH/B268). Sample sizes varied considerably, from n ¼ 75 to n ¼ 79 958 for SPC therapy and n ¼ 73 to n ¼ 383 269 for free-dose combination therapy.…”
Section: Study Populations and Antihypertensive Therapy Prescribedmentioning
confidence: 99%
“…All 29 studies reported on adherence and/or persistence in patients taking SPC therapy for hypertension. Four studies were RCTs (14%) [35,37,38,46]; the remainder (n ¼ 25; 86%) were observational studies [14,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]36,[39][40][41][42][43][44][45]47] (Table S3, http://links.lww.com/HJH/B268). Sample sizes varied considerably, from n ¼ 75 to n ¼ 79 958 for SPC therapy and n ¼ 73 to n ¼ 383 269 for free-dose combination therapy.…”
Section: Study Populations and Antihypertensive Therapy Prescribedmentioning
confidence: 99%
“…A hazai [10,11] és a nemzetközi adatok [12] egyaránt azt igazolták, hogy az egyes vérnyomáscsökkentő készítmények szabad és fix kombinációinak terápiahűsége között átlagosan 20 százalékpontos különbség is lehet, mégpedig a fix kombinációk javára. Mindezek miatt a fix kombinációkat kell előtérbe helyezni az antihypertensiv terápiában [4].…”
Section: Eredeti Közleményunclassified
“…Egy másik hazai vizsgálatunkban egy korszerű ACE-gátló/kalciumcsatornablokkoló és egy ACE-gátló/hidroklorotiazid (HCT) fix kombináció egyéves perzisztenciáját vettük górcső alá. E vizsgálatunkban a több mint 39 000 beteg követése alatt a ramipril/HCT fix kombináció egyéves terápiahűségét 29%-nak találtuk, míg a ramipril/amlodipin fix kombináció perzisztenciája a korábbiaknak megfelelően 54% volt [11]. Eredményünk szerint a ramiprilalapú fix kombinációk közül a ramipril/amlodipin fix kombináció 25 százalékponttal -szignifikánsan -magasabb terápiahűséggel rendelkezett, és ennek megfelelően a ramipril/ HCT elhagyásának kockázata -a ramipril/amlodipin fix kombinációhoz képest -több mint kétszeres volt (HR: 2,318, p<0,001).…”
Section: áBraunclassified